Application of Building Information Modeling (3D and 4D) in Construction Sector in Iraq (Journal of Engineering, 2017)
ABSTRACTBuilding Information Modeling (BIM) is becoming a great known established collaboration process in Architecture, Engineering, and Construction (AEC) industry. In various cases in many countries, potential benefits and competitive advantages have been reported. However, despite the potentials and benefits of BIM technologies, it is not applied in the construction sector in Iraq just like many other countries of the world.The purpose of this research is to understand the uses and benefits of BIM for construction projects in Iraq. This purpose has been done by establishing a framework to application of BIM and identifying the benefits of this technology that would convince stakeholders for adopting BIM in the construction sector in Iraq.Through this research, the use of this technology has been clarified by using the proposed framework (application Revit software and linking it with the MS Project and Navisworks Manage software on the case study) to identify the important benefits to be the beginning to apply the Building Information Modeling technology in the construction sector in Iraq.The research results indicated that such proposed framework can greatly improve the performance of the current state of project management through improving the project quality, cost saving and time-saving.